Hippocampal Gray Volumes Increase in Treatment-Resistant Depression Responding to Vagus Nerve Stimulation. Issue 3 (September 2017) - Perini, Giulia Ida; Toffanin, Tommaso; Pigato, Giorgio; Ferri, Giovanni; Follador, Halima; Zonta, Filippo; Pastorelli, Carlo; Piazzon, Giulia; Denaro, Luca; Rolma, Giuseppe; Ermani, Mario; D'Avella, Domenico
Abstract : Background: Changes in hippocampal gray matter volumes are proposed to be involved in pathogenesis, course, and treatment response of major depressive disorder. Converging evidence suggests that reduced neurogenesis may occur in treatment-resistant depression (TRD). Vagus nerve stimulation (VNS) is a well-defined, long-term brain stimulation treatment for TRD. However, its in vivo positive effect on hippocampal modulation as mechanism of action has never been investigated before in clinical studies. In this study, we intended to explore hippocampal volumetric changes and clinical antidepressant responses in patients with TRD after 6 and 12 months of treatment with VNS. Methods: The TRD outpatients were evaluated for VNS implantation. Right and left hippocampal volumes in 6 TRD patients, who met the criteria for VNS treatment, were measured at baseline before the implantation and after 6 and 12 months. The patients were assessed using Beck Depression Inventory and Hamilton Depression Rating Scale at baseline and at follow-up visits. Results: There was a statistically significant and progressive increase in right and left hippocampal volumes during the follow up ( P < 0.05). Furthermore, patients showed a significant improvement on Hamilton Depression Rating Scale and Beck Depression Inventory scores ( P < 0.05). Conclusions: Our data suggest a VNS modulatory effect on hippocampal plasticity as measured by hippocampal gray volume increase in TRD patients. These preliminary findings indicate the fundamental role of hippocampal remodeling as a marker of response to VNS in TRD.